Python : create-modify-reuse - Knowlton, Jim (Create-modify-reuse guides., 2008)
Python: Create-Modify-Reuse is designed for all levels of Python developers interested in a practical, hands-on way of learning Python development. This book is designed to show you how to use Python (in combination with the raw processing power of your computer) to accomplish real-world tasks in a more efficient way. Don't look for an exhaustive description of the Python language--you won't find it. The book's main purpose is not to thoroughly cover the Python language, but rather to show how you can use Python to create robust, real-world applications. In this respect, the goal is s.